Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the equation [tex]\( 5^{2x} - 20 \cdot 5^{x-1} - 5 = 0 \)[/tex], we can follow these steps:
1. Rewrite the equation in a more manageable form:
Let's make a substitution to simplify the equation. Let [tex]\( y = 5^x \)[/tex]. Then, [tex]\( 5^{2x} \)[/tex] can be written as [tex]\( (5^x)^2 = y^2 \)[/tex], and [tex]\( 5^{x-1} \)[/tex] can be written as [tex]\( \frac{5^x}{5} = \frac{y}{5} \)[/tex].
Substituting these into the equation gives:
[tex]\[ y^2 - 20 \left(\frac{y}{5}\right) - 5 = 0 \][/tex]
2. Simplify the equation:
Simplify the equation by performing the multiplication inside:
[tex]\[ y^2 - 4y - 5 = 0 \][/tex]
3. Solve the quadratic equation:
This is a standard quadratic equation in the form [tex]\( ay^2 + by + c = 0 \)[/tex]. In our case, [tex]\( a = 1 \)[/tex], [tex]\( b = -4 \)[/tex], and [tex]\( c = -5 \)[/tex]. We can solve this using the quadratic formula:
[tex]\[ y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Substituting the values of [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] into the quadratic formula gives:
[tex]\[ y = \frac{-(-4) \pm \sqrt{(-4)^2 - 4(1)(-5)}}{2(1)} \][/tex]
Simplifying inside the square root:
[tex]\[ y = \frac{4 \pm \sqrt{16 + 20}}{2} \][/tex]
[tex]\[ y = \frac{4 \pm \sqrt{36}}{2} \][/tex]
[tex]\[ y = \frac{4 \pm 6}{2} \][/tex]
This gives us two solutions for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{4 + 6}{2} = \frac{10}{2} = 5 \][/tex]
[tex]\[ y = \frac{4 - 6}{2} = \frac{-2}{2} = -1 \][/tex]
4. Back-substitute [tex]\( y = 5^x \)[/tex]:
Recall that we let [tex]\( y = 5^x \)[/tex]. Thus, we have:
[tex]\[ 5^x = 5 \][/tex]
[tex]\[ 5^x = -1 \][/tex]
5. Solve for [tex]\( x \)[/tex]:
For [tex]\( 5^x = 5 \)[/tex]:
[tex]\[ x = 1 \][/tex]
For [tex]\( 5^x = -1 \)[/tex]:
[tex]\( 5^x = -1 \)[/tex] has no real solutions since [tex]\( 5^x \)[/tex] is always positive for any real [tex]\( x \)[/tex]. However, in the complex plane, we can use complex logarithms to solve it.
Recall that for any complex number [tex]\( z \)[/tex], [tex]\( z = e^{i\theta} \)[/tex], hence [tex]\( 5^x = -1 \)[/tex] can be written as:
[tex]\[ x \ln(5) = \ln(-1) \][/tex]
The natural logarithm of [tex]\(-1\)[/tex] is [tex]\( i\pi \)[/tex] (considering the principal value), thus:
[tex]\[ x \ln(5) = i\pi \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{i\pi}{\ln(5)} \][/tex]
Therefore, the solutions to the equation [tex]\( 5^{2x} - 20 \cdot 5^{x-1} - 5 = 0 \)[/tex] are:
[tex]\[ x = 1 \quad \text{and} \quad x = \frac{i\pi}{\ln(5)} \][/tex]
1. Rewrite the equation in a more manageable form:
Let's make a substitution to simplify the equation. Let [tex]\( y = 5^x \)[/tex]. Then, [tex]\( 5^{2x} \)[/tex] can be written as [tex]\( (5^x)^2 = y^2 \)[/tex], and [tex]\( 5^{x-1} \)[/tex] can be written as [tex]\( \frac{5^x}{5} = \frac{y}{5} \)[/tex].
Substituting these into the equation gives:
[tex]\[ y^2 - 20 \left(\frac{y}{5}\right) - 5 = 0 \][/tex]
2. Simplify the equation:
Simplify the equation by performing the multiplication inside:
[tex]\[ y^2 - 4y - 5 = 0 \][/tex]
3. Solve the quadratic equation:
This is a standard quadratic equation in the form [tex]\( ay^2 + by + c = 0 \)[/tex]. In our case, [tex]\( a = 1 \)[/tex], [tex]\( b = -4 \)[/tex], and [tex]\( c = -5 \)[/tex]. We can solve this using the quadratic formula:
[tex]\[ y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Substituting the values of [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] into the quadratic formula gives:
[tex]\[ y = \frac{-(-4) \pm \sqrt{(-4)^2 - 4(1)(-5)}}{2(1)} \][/tex]
Simplifying inside the square root:
[tex]\[ y = \frac{4 \pm \sqrt{16 + 20}}{2} \][/tex]
[tex]\[ y = \frac{4 \pm \sqrt{36}}{2} \][/tex]
[tex]\[ y = \frac{4 \pm 6}{2} \][/tex]
This gives us two solutions for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{4 + 6}{2} = \frac{10}{2} = 5 \][/tex]
[tex]\[ y = \frac{4 - 6}{2} = \frac{-2}{2} = -1 \][/tex]
4. Back-substitute [tex]\( y = 5^x \)[/tex]:
Recall that we let [tex]\( y = 5^x \)[/tex]. Thus, we have:
[tex]\[ 5^x = 5 \][/tex]
[tex]\[ 5^x = -1 \][/tex]
5. Solve for [tex]\( x \)[/tex]:
For [tex]\( 5^x = 5 \)[/tex]:
[tex]\[ x = 1 \][/tex]
For [tex]\( 5^x = -1 \)[/tex]:
[tex]\( 5^x = -1 \)[/tex] has no real solutions since [tex]\( 5^x \)[/tex] is always positive for any real [tex]\( x \)[/tex]. However, in the complex plane, we can use complex logarithms to solve it.
Recall that for any complex number [tex]\( z \)[/tex], [tex]\( z = e^{i\theta} \)[/tex], hence [tex]\( 5^x = -1 \)[/tex] can be written as:
[tex]\[ x \ln(5) = \ln(-1) \][/tex]
The natural logarithm of [tex]\(-1\)[/tex] is [tex]\( i\pi \)[/tex] (considering the principal value), thus:
[tex]\[ x \ln(5) = i\pi \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{i\pi}{\ln(5)} \][/tex]
Therefore, the solutions to the equation [tex]\( 5^{2x} - 20 \cdot 5^{x-1} - 5 = 0 \)[/tex] are:
[tex]\[ x = 1 \quad \text{and} \quad x = \frac{i\pi}{\ln(5)} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.